Effect of Acid Production by Penicillium oxalicum on Physicochemical Properties of Bauxite Residue. Issue 10 (30th October 2020) - Zhang, Yifan; Xue, Rui; He, Xuan; Cheng, Qingyu; Hartley, William; Xue, Shengguo
Abstract: Large-scale discharge of bauxite residue, an alkaline, saline and nutrient-deficient waste material produced in the process of alumina production, has created extreme environments that are challenging to restore. Microbial pathways have been found to play a critical role in the rehabilitation of these residues. In this study, Penicillium oxalicum, an alkali-resistant acid-producing fungus screened from bauxite residue disposal sites, was used to examine its effectiveness for restoration of bauxite residue. By comparing different biomass pretreatment methods, steam explosion pretreatment biomass was added to the medium to enhance microbial metabolism. Following the optimal biomass pretreatment, the contents of organic acids secreted by P. oxalicum were oxalic acid 0.12 mg/mL, formic acid 0.31 mg/mL and acetic acid 0.51 mg/mL, respectively. Addition of pretreatment biomass and microbes significantly lowered bauxite residue pH from 10.9 to 7.2, whilst increasing the electrical conductivity and enzyme activity. Furthermore, the metabolic process of this fungus may promote the release of basic ions dominated by Na + and increase soluble cations. The results suggest that the combined application of biomass and microorganism could reduce the alkalinity of bauxite residue effectively, which may provide theoretical basis and practical reference for bioremediation in the disposal areas.